Winds from the North: Tewa Origins and Historical Anthropology - Jonathan Dombrosky (Ethnobiology Letters, 2014)
Review of Winds from the North: Tewa Origins and Historical Anthropology. Scott G. Ortman. 2012. The University of Utah Press, Salt Lake City. Pp. 520, 51 illustrations, 25 maps, 54 tables. $70.00 (hardcover). ISBN  978-1-60781-172-5.